Responsiveness of Health Professionals to Postabortion Care at a Regional Level Hospital in Ghana: A Qualitative Study of Patients’ Self-Reports - Adde, Kenneth Setorwu; Darteh, Eugene Kofuor Maafo; Kumi-Kyereme, Akwasi; Amu, Hubert (International Journal of Reproductive Medicine, 2018)
Background. The responsiveness of health professionals to patients in the provision of abortion services is essential to influencing patients’ perceptions and expectations regarding the quality of medical care to be received and their general satisfaction. This, in turn, determines if patients will revisit a particular health facility to access abortion services. In this study, we examine the responsiveness of health professionals in providing postabortion care at a regional level health facility in Ghana. Methods. Qualitative data collected from 20 female patients who assessed abortion services at a regional level health facility in Ghana were used. The sample was achieved through saturation while a systematic qualitative orientated text analysis was adopted in analysing the data. Results. Health professionals were responsive to postabortion care at the facility. Most women who sought postabortion care at the facility were referred from other health facilities which could not handle such cases. Other reasons include satisfaction with services received on previous visits to the hospital. We also realized, however, that postabortion services were not covered by the National Health Insurance Scheme. Conclusions. All hospitals across the country should be equipped with the basic equipment and personnel to conduct and manage abortions. This would reduce not only referrals but also possible maternal deaths. Abortion services should also be added to the services covered by the country’s National Health Insurance Scheme.